En ny Maade at drive Biavlen paa, og nye Bikuber (Oversat af Chr. Drewsen.) - Nutt, Thomas (Tidsskrift for Landøkonomi, 2018)
En ny Maade at drive Biavlen paa, og nye Bikuber (Oversat af Chr. Drewsen.)